MAKNA SIMBOLIK DALAM TEKS AJI SARASWATI TRADISI SIWAISME JAWA DAN BALI: SUATU STUDI PERBANDINGAN - Wijayanto, Muhammad Heno; Suparta, I Made (Jurnal Lektur Keagamaan, 2022)
ABSTRACT This study aims to compare the texts of Aji Saraswati (AS) from three texts of Shivaism's traditions in Java and Bali. The data sources used in this study are the texts of Aji Saraswati (AS), Bhimaswarga (BhS), and Jatawedana (JW), which are ancient manuscripts and have transformed into text editions. Philological work steps were carried out to process data in the form of ancient manuscripts and literature studies to collect data in the form of text editions of previous studies. In data analysis, this research used comparative or comparative literature studies. This study found that there are comparisons in the form of similarities and differences in symbolical meaning in structure, written media, and mysticism in Aji Saraswati in various texts from Java to Bali. This comparison can be evidence of the transmission of texts to various regions from Java to Bali. It then rebuts common assumption that this Shivaism literature was originated in Bali and transmitted to the other regions in Indonesia. Keywords: Aji Saraswati, Balinese, Comparative Studies, Javanese, Symbolical Meaning,   ABSTRAK    Penelitian ini bertujuan untuk melakukan perbandingan pada teks Aji Saraswati (AS) dari tiga tradisi teks keagamaan Siwa di Jawa dan Bali. Sumber data yang digunakan dalam penelitian ini adalah teks Aji Saraswati (AS), Bhimaswarga (BhS), dan Jatawedana (JW), baik manuskrip kuno maupun yang sudah menjadi edisi teks. Langkah kerja filologi dilakukan untuk mengolah data yang berupa manuskrip kuno dan studi pustaka untuk mengumpulkan data berupa edisi teks penelitian-penelitian sebelumnya. Dalam analisis data, penelitian ini menggunakan studi sastra bandingan atau komparatif. Hasil dari penelitian ini adalah terdapat perbandingan berupa persamaan dan perbedaan makna simbolik dari struktur, media tulis, maupun mistisme dalam Aji Saraswati di berbagai teks dari Jawa hingga Bali. Perbandingan tersebut dapat menjadi bukti adanya transmisi teks ke berbagai daerah dari Jawa hingga Bali. Studi ini membantah asumsi bahwa literatur Siwaisme berasal dari Bali dan tersebar ke wilayah lain di Indonesia.  Kata kunci: Aji Saraswati, Bali, Jawa, Makna simbolik, Sstudi Perbandingan.